Recurrent Intestinal Obstruction after Radiation Therapy: A Case Report and Review of the Literature - James Nguyen; Amani Jambhekar; Ziyad Nasrawi; Prasad Gudavalli (Case Reports in Surgery)
Introduction. In patients who have undergone resection for rectal cancer after neoadjuvant radiotherapy, loop ileostomy is commonly performed with few serious complications. In rare cases, if this irradiated small bowel is strictured, reversal of the affected ileostomy can have dire consequences. We present a case of a 62-year-old male with recurrent intestinal obstruction after closure of his loop ileostomy. Case Report. RC is a 62-year-old male who initially presented with rectal cancer and underwent neoadjuvant chemoradiation prior to a laparoscopic low anterior resection with diverting loop ileostomy. He underwent elective reversal of his ileostomy and developed persistent postoperative obstruction. He underwent resection of the prior reversal site with normal-appearing dilated proximal bowel loops and collapsed distal bowel loops. He again developed an obstructive picture and underwent resection of the prior anastomosis with creation of an ileocolic anastomosis, after which he recovered well postoperatively. Conclusion. In patients who receive radiation adjuvant therapy for colon cancer, radiation-induced stricture should be considered as a cause of small bowel obstruction postoperative. In the setting of a longstanding ileostomy, evaluation of a defunctionalized distal ileum may be necessary to evaluate potential obstruction from radiation changes.